Global gene expression changes of amniotic fluid cell free RNA according to fetal development. (September 2017) - Jang, Ji Hyon; Jung, Yong Wook; Shim, Sung Han; Sin, Yun Jeong; Lee, Kyoung Jin; Shim, Sung Shin; Ahn, Eun Hee; Cha, Dong Hyun
Abstract: Objective: This study aimed to evaluate the effect of in utero fetal development on the cell-free transcriptome of amniotic fluid by analyzing global gene expression in the amniotic fluid supernatant obtained at different gestational ages from euploid fetuses Study design: Thirteen amniotic fluid samples were obtained from five individuals at 28 gestational weeks and eight individuals at full term pregnancy. Transcriptome data previously analyzed by our group from 14 euploid mid-trimester amniotic fluid samples were used for comparative analysis. RNA was extracted from amniotic fluid supernatants, hybridized to Affymetrix GeneChip Human arrays, and the transcriptome was analyzed using the DAVID toolkit. Results: We evaluated 27 samples, which were divided into three groups as follows: 14 subjects between 16 and 18 gestational weeks from our previous study (group 1), five subjects in late second trimester (group 2), and eight subjects at full term pregnancy (group 3). No genes were significantly differentially regulated between group 3 and group 2. We identified 545 probe sets that were significantly differentially expressed between group 1 and group 2 and 3 samples (FDR P -value <0.05). Based on tissue expression analysis, 396 genes that were upregulated in group 1 were enriched in the nervous system including brain and endocrine organs such as pancreas and adrenal gland. In addition, 136 genes that were upregulated in group 2 and 3 were specific to bronchioepithelial cells. Functional pathway analysis revealed that there was no significantly enriched pathway in terms of genes that were upregulated in either group 2 or group 3. Comparing the amniotic fluid cell-free transcriptome of group 1 and 2 with that of group 3, 18 genes were significantly differently modulated. Conclusions: Fetal development affects the amniotic fluid cell-free transcriptome. Fetal skin keratinization, which begins at 19 gestational weeks, might play an important role in changes in global gene expression in the amniotic fluid.